2015
DOI: 10.1155/2015/453968
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Tissue Surface Adaption of CAD-Designed and 3D Printed Wax Pattern of Maxillary Complete Denture

Abstract: Objective. To quantitatively evaluate the tissue surface adaption of a maxillary complete denture wax pattern produced by CAD and 3DP. Methods. A standard edentulous maxilla plaster cast model was used, for which a wax pattern of complete denture was designed using CAD software developed in our previous study and printed using a 3D wax printer, while another wax pattern was manufactured by the traditional manual method. The cast model and the two wax patterns were scanned in the 3D scanner as “DataModel,” “Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 7 publications
1
28
0
3
Order By: Relevance
“…Although CAD/CAM obturators showed lower misfit values (0.28 ± 0.18) when compared to Heat-cured ones (0.45 ± 0.21), there were no statistical significant differences between both obturator groups at any measured surface. These findings are in line with those of Chen et al (20) who found higher adaption values for CAD/CAM bases.…”
Section: Analysis Of Resulting Miss Fit Of the Two Groupssupporting
confidence: 93%
See 1 more Smart Citation
“…Although CAD/CAM obturators showed lower misfit values (0.28 ± 0.18) when compared to Heat-cured ones (0.45 ± 0.21), there were no statistical significant differences between both obturator groups at any measured surface. These findings are in line with those of Chen et al (20) who found higher adaption values for CAD/CAM bases.…”
Section: Analysis Of Resulting Miss Fit Of the Two Groupssupporting
confidence: 93%
“…Chen et al (20) suggested a digital technique to quantitatively evaluate the tissue surface adaption of a maxillary complete denture wax pattern produced by CAD/CAM. The cast model and the two wax patterns to be evaluated for tissue adaption were separately scanned.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical success, in terms of patient satisfaction and patient preference for the CAD/CAM manufactured CRDPs, has been reported in literature [4][5][6] . In terms of the trueness of the CAD/CAM fabricated CRDPs, when compared to conventional CRDPs, was found to be non-inferior to a conventional PMMA and within the clinically acceptable range [7][8][9][10] . The conventional 'flask-pack-press' technique for the fabrication of CRDPs has been employed for more than half-a-century and can be considered as a time-tested "gold standard" procedure.…”
Section: Introductionmentioning
confidence: 90%
“…A steady evolution and improvement of the technologies, has led to an exponential increase in the number of providers and systems available in the market today [4]. Evidence suggests that CRDPs manufactured by CAD/CAM methods are equivalent or superior to conventionally manufactured CRDPs in terms of accuracy [5][6][7][8][9] and have improved material properties [10,11]. A number of studies have demonstrated very high levels of patient satisfaction with CRDPs constructed with CAD/CAM methods [12][13][14].…”
Section: Introductionmentioning
confidence: 99%